The Glass Ceiling in Politics: Formalization and Empirical Tests - Olle Folke; Johanna Rickne (Research Institute of Industrial Economics (IFN), 2014)
There is a scarcity of women and minorities at the apex of political power. This paper formalizes the concept of the glass ceiling for political organizations and builds on previous research to suggest four testable criteria. A glass ceiling exists if women and/or racial minorities (1) are discriminated against in the organization's promotion process and (2) the discrimination increases in severity for the top levels of power and over an individual's career trajectory. We suggest a series of empirical tests for this phenomenon and apply them to longitudinal data on Swedish politicians. Results show that women face a glass ceiling, while minorities' career disadvantages are more severe at the earlier career steps (a "sticky floor").
Keywords: H10; J16; J21; J45; 330; Glass ceiling; Political careers; Subnational politics; Women and politics; Supply of politicians; Gender inequality; Racial inequality